AKTIVITAS ANTIFUNGI EKSTRAK BIJI JARAK PAGAR (Jatropha curcas L.) TERHADAP PERTUMBUHAN FUNGI Pyricularia oryzae - Zainal Berlian; Syarifah Syarifah; Fitri Astriawati (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2016)
Pyricularia oryzae is a fungus that causes blast disease in rice. Control of this disease usually uses synthetic pesticides, but pesticides have a negative impact on the enviroment and human health. Therefore, control that are enviromentally friendly and safe to apply are needed, using seeds extract of Jatropha curcas. The purpose of this study were to determine the ability of Jatropha seed extract and to determine the optimum concentration of Jatropha seed extract in inhibiting the growth of Pyricularia oryzae in vitro. The research was conducted at Hall Crop Protection South Sumatra. Jatropha seeds powder was extracted with maceration method using ethanol 96%. Antifungal test was done by using a modification of agar diffusion method by using cork choler and the concentration used were 0% (v/v), 25% (v/v), 50% (v/v), and 100% (v/v). Data obtained were growth diameters of fungus Pyricularia oryzae and analyzed by ANSIRA and BNT test. The results showed that Jatropha seed extract can inhibit the growth of Pyricularia oryzae in vitro. The optimum concentration of Jatropha seed extract was 100% with the smallest growth diameter average of the fungus 3,66 cm and the biggest inhibition percentage 59,3%.